Mortonagrion megabinluyog spec. nov. from Brunei (Odonata: Zygoptera: Coenagrionidae) - Dow, Rory A.; Choong, Chee Yen (Zootaxa, 2015)
M. megabinluyog spec. nov. is described from a location in Brunei on the island of Borneo. Additional illustrations of its sister species M. astamii are provided.